Cardiovascular Impacts on COVID-19 Infected Patients - Raghavan, Somasundaram; Gayathri, R.; Kancharla, Sudhakar; Kolli, Prachetha; Ranjitha, J.; Shankar, Vijayalakshmi (Frontiers in Cardiovascular Medicine, 2021)
The SARS-CoV-2 virus has taken more than 2 million lives on a global scale. Over 10 million people were confirmed with COVID-19 infection. The well-known spot of primary infection includes the lungs and the respiratory system. Recently it has been reported that the cardiovascular system and coagulation mechanisms were the second major targets of biological system affected due to the viral replication. The replication mechanism of SARS-CoV-2 involves the angiotensin-converting enzyme 2- (ACE2) surface receptors of endothelial cells belonging to various organs which act as the binding site for the viral spike (S) protein of SARS-CoV-2. The COVID-19 virus has been recently listed as a primary risk factor for the following cardiovascular conditions such as pericarditis, myocarditis, arrhythmias, myocardial injury, cardiac arrest, heart failure and coagulation abnormalities in the patients confirmed with COVID-19 viral infection. Direct and indirect type of tissue damage were the two major categories detected with cardiovascular abnormalities. Direct myocardial cell injury and indirect damage to the myocardial cell due to inflammation were clinically reported. Few drugs were clinically administered to regulate the vital biological mechanism along with symptomatic treatment and supportive therapy.